PKM Community Partnership Program: Strengthening the Capacity of the Salenrang Village Community, in Optimizing the Management of Geopark Area Geotheritage, Maros Regency South Sulawesi Province - Haerany Sirajuddin; Hendra Pachri; A. M. Imran; Jamal Rauf Husain; Rohaya Langkoke; Ratna Husain; Meutia Farida; Adi Maulana; Sultan .; Agustinus .; Meinarni Thamrin; Safruddim .; Bahrul Hidayah; Muh. Fajrin; Muh. Zulfahmi Azrul; Nurul Ikhsan (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2024)
Indonesia is a country that has many islands and is rich in tourist destinations such as natural tourism, history, religion, culture, and so on. This attracts foreign tourists to visit or travel to Indonesia. One of the leading destinations in South Sulawesi which attracts foreign and domestic tourists is the Rammang-Rammang Karst in Maros which is known as the largest karst in Indonesia and is also a Global Karst Geopark Area approved by UNESCO. Rammang-Rammang Karst is an area that has a unique panorama, namely the type of karst, namely, tower karst with the natural landscape shape (geomorphology) of the Maros-Pangkep Karst area. Increasing the capacity of the Salenrang Village community is urgently needed so that the dissemination of geology-based information is more optimal. Therefore, the Department of Geological Engineering, Faculty of Engineering, Hasanuddin University, in collaboration with the Salenrang Village Government, organized a Laboratory Based Education (LBE) Service to increase the capacity of the people of Salenrang Village, Maros Regency. The methods used in this LBE event are observation, socialization and presenting information on tourist destinations through pamphlets and brochures. The observation method is carried out with the aim of systematically obtaining data on objects that will be socialized at the LBE service location in detail. Socialization was carried out to the Salenrang Village community about the tourism potential and geological conditions of the Rammang – Rammang Karst by distributing brochures and pamphlets to the Salenrang Village community in the LBE event area. Based on the results of the questionnaire, around 63% of visitors understand geological information in the tourist area, making it a challenge to disseminate better information. Through this LBE event, the people of Salenrang Village have proven that scientific information related to geological characteristics is very helpful in managing the geoheritage of the Rammang Rammang Area so that the increase in visitors will increase.